Correlation of Ontology of Science in the Concept of Educational Management - Nining Huriati; Ahmad Syukri SS; Badarussyamsi; Andam Yulianti; Muhammad Taher; Mufida Maryamah Gustia (Darul Ilmi Bina Insan Foundation, 2025)
This article examines the ontological aspects of knowledge within the perspective of philosophy and its connection to educational management. Ontology, as a branch of philosophy that explores the nature of being and reality, provides a foundational framework for the development of knowledge, including education. In the context of educational management, ontology serves as a basis for understanding the reality, existence, and underlying values of educational systems. This approach enables the application of principles such as sustainability, meaningfulness, and empowerment in educational management. The article also explores the relevance of ontological philosophy in building a value-based framework for educational management, including curriculum development, human resource management, and the adoption of technological innovation in education. Furthermore, integrating ontology into modern educational management addresses the challenges of the digital era by ensuring that educational objectives remain relevant and adaptive to changing times. This study aims to foster a deeper understanding of the importance of ontological philosophy as a foundation for holistic and meaningful educational management.